Memorable Tourism Experience and Service Quality on Revisit Intention with Customer Satisfaction as Mediating Variable (Study at Saloka Theme Park, Semarang Regency, Central Java) - Iqbal Ramdhani, Muhammad; Pranaditya, Ari; Shabibah, Khansa (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to investigate the mediating role of customer satisfaction in the relationship between memorable tourism experience (MTE) and service quality on visitors’ revisit intention at Saloka Park, a thematic recreational park located in Semarang Regency, Central Java. This research is expected to explore the relationships among several influencing factors and emphasize the importance of creating memorable tourism experiences as well as maintaining service quality to enhance customer satisfaction, which subsequently drives the intention to revisit Saloka Park. Using a quantitative approach and survey method, data were collected from Saloka Park visitors and analyzed using path analysis techniques. The findings revealed that both memorable tourism experience (MTE) and service quality exert a positive and statistically significant impact on customer satisfaction. Furthermore, customer satisfaction was proven to mediate the relationship between MTE and service quality on revisit intention. These findings highlight the critical role of delivering memorable tourism experiences and maintaining high service quality in enhancing customer satisfaction, which subsequently promotes revisit intentions. The practical implication of this study is that recreational park managers can focus on improving visitor experiences and service quality as key factors to retain and enhance visitor loyalty